Exporting Jihad: Iran's Use of Non-State Armed Groups - O'Brien, James M. (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper examines Iran's use of non-state armed groups to achieve its political and security objectives. It recognizes the use of non-state armed groups as being a critical component to an Iranian security doctrine that is guided by strategic asymmetry. Specifically, it examines: the political and strategic cultures that contribute to the use of non-state armed groups; the structural components that facilitate their use; the operational particulars of the groups which Iran utilizes; the broader implications of their strategic employment. To achieve this qualitative study, this paper uses an architecture for the study of non-state armed groups. This architecture was developed by Professors Richard Shultz, Douglas Farrah, and Itamara Lochard in the US Air Force INSS Occasional Paper (57), entitled Armed Groups: A Tier-One Security Policy. This framework provides four categories of non-state armed groups, and it utilizes six variables for the analysis of individual groups. Analysis leads this study to conclude the following: Iran's senior leadership sees the exportation of jihadi insurgencies as paramount to achieving its long-term ideological goals.